Low temperature exciton-exciton annihilation in amphi-PIPE J-aggregates - C. Spitz; S. Daehne (International Journal of Photoenergy)
The mobility of optically excited excitons on J-aggregates can be demonstrated by the phenomena of exciton-exciton annihilation. In this intensity-dependent process the collision of two excitons results in their annihilation and hence in a shortening of the mean excitation lifetime. By measuring the intensity-dependent fluorescent lifetime in contrast to the predicted immobilization of the excitons at low temperature we could prove the excellent mobility of the excitons at a temperature (4K), which is far below their expected freezing point.